The Effect of Working Posture on Physical Fatigue Among Textile Workers with Age, Length of Service, and Body Mass Index as Covariates - Sumardiyono, Sumardiyono; Suratna, Farhana Syahrotun Nisa; Chahyadhi, Bachtiar; Widjanarti, Maria Paskanita; Wijayanti, Reni; Ulfah, Nur (Media Publikasi Cendekia Indonesia, 2025)
Physical fatigue among textile workers is caused by non-ergonomic working postures (e.g., prolonged standing) and personal characteristics such as age, length of service, and body mass index (BMI). The objective of the present investigation was to study the effect of working posture on physical fatigue after adjusting for the covariates of age, length of service, and BMI. An analytical cross-sectional study with a quantitative design was applied to 174 Surakarta workers selected by stratified random sampling. Work posture was categorized under standing and sitting, while physical fatigue was measured by the Subjective Self Rating Test (SSRT) questionnaire. ANCOVA via SPSS version 27 software was applied for the analysis, in which age, length of service, and BMI were employed as covariates. The findings indicated that the standing posture was strongly influenced positively on physical fatigue (Partial Eta Squared = 0.547, p < 0.001), and the effect size is large. Significant risk factors were also found to be age (p = 0.012) and BMI (p = 0.035), but the length of service was not significant (p = 0.084). The ANCOVA model also showed excellent predictability values of adjusted R 2 = 0.715, which implied that the model was able to explain 71.5 percent of the physical fatigue. These findings emphasize the importance of posture-based ergonomic interventions to prevent fatigue and improve occupational health in the textile industry